Canadian journal of pure and applied sciences - Fahrul Huyop, author; Ng, Hong Jing, author; Ronald A. Cooper, author; Canadian Journal of Pure and Applied Sciences, 23 Ogos 2007). (Johor Bahru, Johor : Penerbit Jurnal Akademik, 2013)
Bibliography: p .5.